(untitled) (Academicia Globe: Inderscience Research, 2022)
Today’s world visual art is developing at a fast pace and in different streams and directions. but it cannot be said that this process is happening in the same way in all provinces. Realism is gaining popularity in one country, impressionism in another, and abstractionism in another. In general, countries such as France, Mexico, the USA, Spain, and Russia are leading the development of visual arts in the late 19th and early 20th centuries.